Operant conditioning of autogrooming in vervet monkeys: Cercopithecus aethiops - Iversen, Iver H. (1984)
Vervet monkeys received food reinforcement contingent on autogrooming. Experiment 1 reinforced grooming on a schedule of increasing intermittency and grooming increased in frequency and duration; with only pauses reinforced, grooming decreased in frequency and duration. Experiment 2 demonstrated differentiation of operant autogrooming; in each session a different single form of grooming was reinforced (for example, grooming the tail only), and that form increased in frequency while other forms became less frequent. In Experiment 3 scratching was succesfully conditioned with a method that selectively reinforced variety in behavior; reinforcement was contingent on a shift in scratching form. In Experiment 4, with no contingencies on grooming, a prefood stimulus did not increase autogrooming whether or not grooming had previously resulted in contingent reinforcement. The form of conditioned autogrooming resembled the form of unconditioned autogrooming. The discussion suggests how reinforcement principles can account for changes in the topography of operant behavior.